PENYELESAIAN KREDIT BERMASALAH DENGAN JAMINAN SURAT KEPUTUSAN PEGAWAI NEGERI SIPIL TERHADAP PEGAWAI NEGERI SIPIL YANG DIPECAT (STUDI PADA PT. BANK ACEH CABANG KOTA SABANG) - SOFYATI ALFYANA (PREMISE LAW JURNAL, 2017)
Article 3, paragraph (1) of the Directive of Board of Directors of Bank Indonesia No. 23/69/KEP/DIR, on February 28, 1991 regarding Guarantee in Giving Credit states that guarantee is confidence of a Bank in debtor’s capacity to pay off his credit according to what has been agreed. In practice, there is the use of the Directive for Goverment Employee as a mortgage which will risk the Bank in giving a credit, let alone if the government employee is dismissed before retiring. The research used descriptive analytic method which described, explained, and analyzed the implementation of execution on non-performing loan by using the Directive for Government Employee, the position of mortgage, using the Directive for Government Employee when the debtor was dismissed, and the attempt of PT Bank Aceh, Sabang Branch, to settle non-performing loan when the debtor was dismissed. Keywords: Credit, Mortgage, Directive for Government Employee